DETEKSI VARIASI SOMAKLONAL PLANLET Jatropha curcas Linn. HASIL REGENERASI EMBRIO SOMATIK DENGAN MARKA MOLEKULAR ISSR - . Rudiyanto; Darda Efendi; Erwin Al-Hafiizh; Tri Muji Ermayanti (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2021)
Physic nut (Jatropha curcas Linn.) has the potential as a source of sustainable biofuels. Somatic embryo proliferation of J. curcas may cause somaclonal variations. This research aimed to investigate somaclonal variations of J. curcas somatic embryo derived-plantlet using ISSR markers. Somatic embryos of J. curcas at the globular phase were cultured on liquid MS medium supplemented with 0, 0.5, 1.0, 1.5, and 2.0 mg L-1 of 2,4-D. Parameter observed were embryos weight, embryos volume, colour, and size of embryos. After proliferation, the embryos were cultured on a germination medium until the cotyledonary phase. The results showed that proliferation of J. curcas somatic embryos was optimal, with the highest weight and volume,  at MS medium added with 1 mg L-1 2,4-D.